Deletion of MtrA Inhibits Cellular Development of Streptomyces coelicolor and Alters Expression of Developmental Regulatory Genes - Zhang, Peipei; Wu, Lili; Zhu, Yanping; Liu, Meng; Wang, Yemin; Cao, Guangxiang; Chen, Xiu-Lan; Tao, Meifeng; Pang, Xiuhua (Frontiers in Microbiology, 2017)
The developmental life cycle of Streptomyces species includes aerial hyphae formation and spore maturation, two distinct developmental processes that are controlled, respectively, by two families of developmental regulatory genes, bld and whi. In this study, we show that the response regulator MtrA (SCO3013) is critical for normal development of aerial hyphae in S. coelicolor and related species. ΔmtrA, a deletion mutant of the response regulator gene mtrA, exhibited the bald phenotype typical of bld mutants defective in aerial mycelium formation, with formation either much delayed or absent depending on the culture medium. Transcriptional analysis indicated that MtrA activates multiple genes involved in formation of aerial mycelium, including chp, rdl, and ram genes, as well as developmental regulatory genes of the bld and whi families. However, the major regulatory gene bldD showed enhanced expression in ΔmtrA, suggesting it is repressed by MtrA. EMSAs indicated that MtrA binds upstream of several genes with altered expression in ΔmtrA, including bldD and whiI, and sequences similar to the consensus binding sequence for MtrA of another actinomycete, Mycobacterium tuberculosis, were found in the bound sites. A loosely conserved recognition sequence containing two short, direct repeats was identified for MtrA of S. coelicolor and was validated using mutational analysis. MtrA homologues are widely distributed among Streptomyces species, and as with S. coelicolor, deletion of the mtrA homologues sve_2757 from S. venezuelae and sli_3357 from S. lividans resulted in conditional bald morphology. Our study suggests a critical and conserved role for MtrA in Streptomyces development.